Pengaruh DER dan ROE terhadap Nilai Perusahaan Asuransi yang Terdaftar di BEI Periode 2020–2024 - Nur Varicha Arvin Agustin; Fajrin Maulidiana Kirom (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the effect of Debt to Equity Ratio (DER) and Return on Equity (ROE) on firm value in insurance companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024. Firm value is measured using Price to Book Value (PBV) as the main indicator. The method used in this research is a quantitative approach with a causal associative research type. The data used is secondary data obtained from the annual financial statements of insurance companies. The analysis was carried out using a panel data regression model with the STATA application, through the Common Effect Model, Fixed Effect Model, and Random Effect Model test stages.